2017
DOI: 10.1111/apa.13788
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutritional practices in premature infants can increase their growth velocity and the breastfeeding rates

Abstract: Introducing nutritional practices such as the increased use of breastmilk and the breastfeeding rate improved GV over the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
2
0
4
Order By: Relevance
“…In addition, some studies support the fact that strategies such as fortification have allowed to reconcile 2 current challenges observed in neonatal care units: increasing the GR of preterm newborn infants without affecting breastfeeding rates. 23 A fair amount of evidence supports the association between an adequate GR and a lower risk for death after discharge or severe disability. Several studies and systematic reviews have demonstrated a positive association between an adequate weight gain and better cognitive results in an age range from 12 months to 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies support the fact that strategies such as fortification have allowed to reconcile 2 current challenges observed in neonatal care units: increasing the GR of preterm newborn infants without affecting breastfeeding rates. 23 A fair amount of evidence supports the association between an adequate GR and a lower risk for death after discharge or severe disability. Several studies and systematic reviews have demonstrated a positive association between an adequate weight gain and better cognitive results in an age range from 12 months to 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, hay estudios que apoyan que estrategias como la fortificación han permitido conciliar dos retos actuales de las unidades de cuidados neonatales: aumentar la VC de los niños prematuros sin un detrimento de las tasas de lactancia materna. 23 Existe bastante evidencia que avala la asociación entre una adecuada VC y un menor riesgo de muerte tras el alta o de discapacidad grave. Numerosos estudios y revisiones sistemáticas muestran una asociación positiva entre una adecuada ganancia ponderal y mejores resultados cognitivos en rangos de edad de entre los 12 meses y los 19 años.…”
Section: Discussionunclassified
“…A principal causa de mortalidade neonatal no mundo foi o nascimento prematuro (< 37 semanas de idade gestacional) (15,4%), seguida das complicações relacionadas ao intraparto (10,5%) e sepse neonatal (6,7%) (LIU et al, 2015). Segundo o UNICEF (Fundo das Nações Unidas para a Infância), mais de 80% das mortes de recém-nascidos (RN) são resultados destas causas, especialmente o parto prematuro, as complicações durante o trabalho de parto e parto e as infecções como sepse, meningite e pneumonia (UNITED NATIONS CHILDREN'S FUND, 2018).…”
Section: A Prematuridade No Contexto Da Saúde Públicaunclassified
“…Todos os anos nascem quinze milhões de prematuros em todo o mundo (WORLD HEALTH ORGANIZATION, 2012a; UNITED NATIONS CHILDREN'S FUND, 2018), e o Brasil é um dos dez países com maior número destes nascimentos, apresentando taxas altas e crescentes. Apesar dos avanços nas tecnologias de cuidados neonatais e subsequente maior sobrevida desses prematuros, a prematuridade contribui para 45% das mortes entre os RN brasileiros (WORLD HEALTH ORGANIZATION, 2012a).…”
Section: A Prematuridade No Contexto Da Saúde Públicaunclassified
See 1 more Smart Citation